TEORI EFEKTIVITAS PADA PROSEDUR PEMERIKSAAN PERKARA DI PENGADILAN TATA USAHA NEGARA - Cindyva Thalia Mustika; Nisa Amalina Adlina (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
The purpose of this research is first to discover the development of case examination procedures in the current State Administrative Court. Second, to determine the current case examination procedure in the State Administrative Court associated with the Theory of Effectiveness. The type of research used is normative research which places the law as a system of norms, with descriptive analytical methods, namely by describing existing problems and analyzing them. The results of this study show First, there has been an expansion of the competence of the State Administrative Court in receiving, examining & adjudicating a case. The State Administrative Court Law that has not regulated this has resulted in a procedural law vacuum so that the Supreme Court in the 2011-2017 timeframe issued its legal products in the form of Supreme Court Regulations, namely the State Administrative Court Law which previously only regulated 3 types of case examination procedures, namely ordinary examination, simple examination, and rapid examination, currently there are several new case examination procedures regulated in 5 Supreme Court Regulations. Second, in terms of one of the factors in the Theory of Effectiveness, namely the legal factor itself (the law), this factor states that to determine whether a written law functions or not depends on the rule of law itself, one measure of the success of this factor is that the existing rules regarding certain areas of life are quite synchronous / there is no horizontal conflict & hierarchy, but the current main regulation, namely the State Administrative Court Law, in fact has not been synchronised with other regulations issued by the Supreme Court in the form of Supreme Court regulations which aim to fill the void of procedural law, especially the law of examination.